Decolorization of azo dye Everdirect Supra Red BWS in an aqueous solution by heat-activated persulfate: optimization using response surface methodology - Tunc, Muslun Sara (Desalination Publ, 2019)
In this study, the removal of Everdirect Supra Red BWS dye via a heat-activated persulfate process was studied. Individual and interactive effects of important process parameters, that is, persulfate concentration, initial dye concentration, process temperature and reaction time, were investigated using the response surface methodology. The high determination coefficient value (R-2 = 0.9948) of the quadratic model showed that the model was accurate in predicting the experimental results. The experimental results corresponded well with the predicted models. Using the desirability function, the optimum conditions were found to be 2,375 mg L-1 persulfate concentration, 87.51 mg L-1 dye concentration, 62.5 degrees C process temperature and 35 min reaction time, which resulted in the dye removal efficiency of 97.63%. The effects of radical scavengers on the dye degradation were also evaluated. The results indicated that SO4 center dot- was more dominant in the oxidation process. Moreover, the effect of various salts such as Na2SO4 and Na2CO3 on the dye removal was also examined. The dye removal level slightly decreased in the presence of Na2SO4, while Na2CO3 did not cause a negative effect on the performance of this process.
Keywords: Everdirect Supra Red BWS; Persulfate; Response surface methodology; Sulfate radical